2009
DOI: 10.1080/13547500902730664
|View full text |Cite
|
Sign up to set email alerts
|

Plasma total homocysteine level and methylenetetrahydrofolate reductase 677C>T genetic polymorphism in Japanese patients with rheumatoid arthritis

Abstract: Hyperhomocysteinemia is a known risk factor of cardiovascular disease. Homocysteine has been also linked to inflammation in rheumatoid arthritis (RA). In this study, we investigated the relationship between plasma homocysteine levels and single nucleotide polymorphism (SNP) of the gene coding for methylenetetrahydrofolate reductase (MTHFR), an enzyme involved in the biosynthesis of homocysteine, and the correlation between the plasma homocysteine levels and generally used inflammatory markers (C-reactive prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
0
11
0
3
Order By: Relevance
“…In the literature, the association between MTHFR C677T mutation and hyperhomocysteinemia has been confirmed by various authors [Almawi et al, 2009;Fujimaki et al, 2009;Husemoen et al, 2009;Oterino et al, 2010;Szamosi et al, 2009;Yamada et al, 2001] although in another study [Antoniades et al, 2009] the same mutation showed a stronger correlation with low folate levels. In our study we did not analyze folate levels; however, according to several studies, low levels of folate are inversely related to homocysteine levels [Cadoni et al, 2004;Quaranta et al, 2008;Schuknecht et al, 1973;Suckfüll et al, 2002].…”
Section: Discussionmentioning
confidence: 73%
“…In the literature, the association between MTHFR C677T mutation and hyperhomocysteinemia has been confirmed by various authors [Almawi et al, 2009;Fujimaki et al, 2009;Husemoen et al, 2009;Oterino et al, 2010;Szamosi et al, 2009;Yamada et al, 2001] although in another study [Antoniades et al, 2009] the same mutation showed a stronger correlation with low folate levels. In our study we did not analyze folate levels; however, according to several studies, low levels of folate are inversely related to homocysteine levels [Cadoni et al, 2004;Quaranta et al, 2008;Schuknecht et al, 1973;Suckfüll et al, 2002].…”
Section: Discussionmentioning
confidence: 73%
“…They also anticipated that homocysteine might not only reflect the inflammatory status in RA patients but also predict the efficacy and adverse reactions of anti-RA therapy (Fujimaki et al 2009). …”
Section: Discussionmentioning
confidence: 98%
“…5,18 Relatou-se que os níveis de homocisteína plasmática estão relacionados com marcadores inflamatórios em alguns pacientes com AR. 16,17 Isso concorda com os dados encontrados no presente estudo, que indicam uma relação entre o VHS e os níveis de homocisteína nos indivíduos estudados.…”
Section: Tabela 2 -Distribuição Dos Genótipos (Polimorfismos No Gene unclassified
“…[15][16][17] Cada vez mais estudos de farmacogenética mostram que diversos polimorfismos de genes, incluindo a variante TS-5' UTR 3R/2R, resultam em hiper-homocisteinemia, que poderia ser responsável pelos efeitos adversos mais comuns e graves relacionados com o MTX. 7,17,18 Além disso, a hiper-homocisteinemia tem sido associada à inflamação na AR.…”
unclassified
See 1 more Smart Citation